THE ROLE OF SARAWAK MUSEUM IN SUSTAINING THE SARAWAK HERITAGE - Nur Auni, Ugong; B. B. B., Bee (UMS Publiser, 2023)
Cultural and social transformations in the modern era have highlighted the significance of museums in ensuring the survival of our past for future generations. As a non-profit, permanent organization that explores, gathers, maintains, interprets, and shows tangible and intangible legacies, the museum offers different experiences for education, enjoyment, contemplation, and knowledge sharing. This research used a descriptive qualitative approach to show that the Sarawak Museum Department has been effective since 1947 in protecting Sarawak’s cultural heritage. The duty of the museum includes activities such as collecting, identifying, recording, conserving, protecting, and preserving the heritage, as well as assuring the transmission of the Sarawak heritage to subsequent generations through educational programming and exhibition.